2020
DOI: 10.1021/acs.orglett.0c03385
|View full text |Cite
|
Sign up to set email alerts
|

A CTV Analogue: Arene-Persubstituted Cyclotrixylohydroquinoylene and Its Derivatives

Abstract: A crown-shaped cyclotriveratrylene (CTV) analogue with persubstituted arene unitsnamely, cyclotrixylohydroquinoylene (CTX)was synthesized from tetrasubstituted o-xylohydroquinone. Importantly, a series of CTX derivatives were prepared by introducing second bridged methylene, phenylphosphine oxide, and dimethylsilyl at the middle rim, referred to as CTX­[CH 2 ], CTX­[P­(O)­Ph], and CTX­[SiMe 2 ], respectively, with the completely locked crown conformation, leading to the formation of unique C3-symmetric C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 52 publications
2
9
0
Order By: Relevance
“…The observed texture pattern of the columnar hexagonal phase is further correlated with the self-organized molecular pattern, as confirmed by XRD study. [26] All four compounds exhibited a higher temperature range of mesophase and thermal stability, persisting up to 19.0 °C during the cooling cycle (CTGF 4 ). On the other hand, we observed that increasing the flexibility of the side-alkyl spacer can impact the crystallinity of the compounds.…”
Section: Pom and Thermal Behaviormentioning
confidence: 98%
See 1 more Smart Citation
“…The observed texture pattern of the columnar hexagonal phase is further correlated with the self-organized molecular pattern, as confirmed by XRD study. [26] All four compounds exhibited a higher temperature range of mesophase and thermal stability, persisting up to 19.0 °C during the cooling cycle (CTGF 4 ). On the other hand, we observed that increasing the flexibility of the side-alkyl spacer can impact the crystallinity of the compounds.…”
Section: Pom and Thermal Behaviormentioning
confidence: 98%
“…Importantly, the previous study confirmed the use of fluorescein as a linker unit supports the formation of columnar hexagonal phase with higher temperature range of mesophase and light-emitting properties. [26] All four symmetrical tri-substituted CTG-based compounds adopted a crown conformation and displayed a columnar hexagonal type mesophase. The liquid crystalline phase is exhibited under both heating and cooling conditions.…”
Section: Pom and Thermal Behaviormentioning
confidence: 99%
“…CTX[P(O)Ph] was synthesized in our previous work in just two steps with high thermal stability. [11] Despite the low surface area, the CTX[P(O)Ph] powder exhibited high performance for both vapor iodine adsorption (0.76 g/g) and aqueous iodine adsorption. In addition, the adsorbent could be regenerated by heating under vacuum and the good reusability was achieved.…”
Section: Introductionmentioning
confidence: 99%
“…We supposed the iodine could locate inside or outside the cavity of CTX[P(O)Ph] because the benzene rings and P=O moieties could provide extra noncovalent binding sites for iodine molecules. CTX[P(O)Ph] was synthesized in our previous work in just two steps with high thermal stability [11] . Despite the low surface area, the CTX[P(O)Ph] powder exhibited high performance for both vapor iodine adsorption (0.76 g/g) and aqueous iodine adsorption.…”
Section: Introductionmentioning
confidence: 99%
“…CTX then could be bridged with methylene groups at its middle rim and then was successfully oxidized to obtain the water-soluble carboxylate-based macrocycle WCTX[CH 2 ]. [18] However, the overall low yield limits its further application, and it is of great significance to construct a phospholate-based water-soluble macrocycle, because it is well known that phosphoric acids and their salts are more biocompatible in biology system. [19] Therefore, herein, biocompatible water-soluble phospholate-based CTX (WPCTX) was prepared by connecting the adjacent hydroxyl groups with phosphoric acid at its middle rim of CTX just in two steps with satisfying yield (Figure 1).…”
Section: Introductionmentioning
confidence: 99%